Efeitos da doxicilina na hipertensão arterial induzida pela exposiçao ao chumbo: quantificação de pepídeos vasoativos - Nascimento, Regina Aparecida do [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work was investigated the participation of MMP's in acute lead intoxication, as well as if doxycycline reverses the lead-induced hypertension,and whether there arechanges in CGRP (calcitonin gene related peptide),adrenomedullin or endothelinplasma levels afterlead-induced hypertension.40 Wistar young adult male rats(weighting 200g) were used. Pb group (n=12) was intoxicated with lead acetate (1st dose 8μg/100g of body weight, and subsequent doses 0.10 μg/100g, intra-peritoneal to cover daily loss, during seven days) and treated with doxycycline (30mg/kg of body weight) (Pb+Doxy group, = 12) or saline (Pb group, = 12) by gavage, once a day. Control groups (n=8) received sodium acetate in order to offer the same amount of acetate molecules asPb group. Control group was also treated with doxycycline (Doxy group, n=8). All treatments were performed for seven days. Lead concentrations in whole blood were determined by graphite furnace atomic absorption spectrometry. Plasma adrenomedullin, CGRP, endothelin and MMP-2 concentrations were evaluated using commercials enzyme immunoassays (ELISA) kits. All experiments were approved by the Institution ethics committee (protocol nº 458/2013). There was an increase (P<0.05) in the systolic blood pressure of Pb group (167 mmHg vs. 142 ± 2 ou 143± 3 mmHg in Control group), however, doxycycline showed a decrease in these values (137± mmHg in Pb+Doxy group). The lead concentrations in blood were significantly increased in both intoxicated groups (Pb and Pb+Doxy groups) which presented 10μg/dL±1,0 μg/dLvs. 2μg/dL±1,0 μg/dL, in non-intoxicated groups (Saline or Doxy groups). Doxycycline reversed the reduction of 45% in the levels ofadrenomedullin induced by lead (Pb group presented 0.43 pg/mL vs. 1.0 pg/mL in Pb+Doxy group). We did not observe changes in the plasmatic levels of CGRP, endothelin and MMP-2.We suggest that hypertension induced by lead exposure (8 μg/100g ...

Neste trabalho foi investigado a participação de MMP's na intoxicação aguda por chumbo, bem como se a doxiciclina reverte a hipertensão induzida pelo chumbo e a alteração dos níveis plasmáticos de CGRP- (peptídeo relacionado ao gene da calcitonina), adrenomedulina ou endotelina após hipertensão induzida pelo chumbo. Utilizamos 40 ratos machos Wistar adultos jovens (pesando 200g). Grupo Pb (n=12) foi intoxicado com acetato de chumbo (1ª dose 8 μg /100g do rato, e subsequentes doses 0.1μg/100g intra-peritoneal para cobrir a perda diária, durante sete dias) e tratados com doxiciclina 30mg/kg/dia do rato (Pb+Doxy = 12) via oral uma vez ao dia. Grupo controle (n=8) recebeu acetato de sódio para oferecer quantidade equimolar de moléculas de acetato do grupo Pb. Grupo controle também foi tratado com doxiciclina (Grupo Doxy, n=8). Todos os tratamentos foram realizados por sete dias. A concentração em chumbo em sangue total foi determinada em forno de grafite por espectrometria de absorção atômica. Concentrações plasmáticas de adrenomedulina, CGRP, endotelina e MMP-2 foram avaliadas usando kits comerciais de imunoensaio enzimático (ELISA). O comitê de ética institucional (protocolo nº 458/2013) aprovou todos os experimentos. Houve aumento na pressão sistólica (grupo Pb 167 ± mmHg vs. 142 ± 2 ou 143 ± 3 mmHg no grupo controle) (P<0.05), entretanto, doxiciclina mostrou diminuir valores (137 ± 3 mmHg no grupo Pb+Doxy). A concentração de chumbo no sangue foi significativamente aumentada em ambos os grupos intoxicados (Pb e Pb + Doxy) que apresentou 10μg/dL (± 1,0) vs. 2,0 μg/dL (± 1,0) em grupos não intoxicados (grupos Controle ou Doxy). Doxiciclina reverteu a redução de 45% nos níveis de adrenomedulina induzido pelo chumbo (grupo Pb apresentou 0.43 (± 0,2) vs. 1.0 pg/mL (± 0,2) em grupo Pb+Doxy). Não observamos mudança nos níveis plasmáticos de CGRP, endotelina e MMP-2. Sugerimos que a hipertensão...
Keywords: Peptídeos; Hipertensão; Chumbo no organismo; Agentes antibacterianos; Anti-infecciosos; Lead in the body